Hakikat Peserta Didik: Studi Kepustakaan - Aisyah Miftakhul Jannah (Jurnal Pendidikan Tuntas, 2026)
Learners are the primary element in the educational process, possessing potential, human nature (fitrah), and the ability to develop through appropriate guidance and learning. In the philosophy of Islamic education, learners are viewed as a trust (amanah) from Allah SWT, endowed with intellectual, spiritual, emotional, and social dimensions that need to be balanced through education based on Islamic values. This article aims to discuss the nature of learners from the perspective of Islamic education philosophy, covering their definition, characteristics, potential, and position in the educational process. This study utilizes a literature review method by examining various relevant sources, including the Qur'an, hadith, books, and scientific journals. The results of the study show that learners are not only the objects of education but also active subjects in developing their potential toward becoming individuals with faith, knowledge, and noble character. Learners at the Islamic Elementary School (Madrasah Ibtidaiyah/MI) and Elementary School (SD) levels possess characteristics such as high curiosity, being active, easily imitating, and requiring engaging learning as well as exemplary models from educators. Therefore, educators do not only act as conveyers of knowledge but also as guides capable of understanding the needs and development of learners so that the learning process runs effectively, humanely, and meaningfully. Understanding the nature of learners serves as an essential foundation in realizing the goals of Islamic education, which is to form a generation capable of developing their entire potential optimally as a perfect human being (insan kamil).